Information technology as a sources of competitive advantage in international education - Mazzarol, T.; Hosie, Peter; Jacobs, S. (Triangle Journals Ltd, 1998)
International education has emerged as a significant global industry. Over a million students study outside their country of origin, usually paying substantial annual fees to foreign institutions. A recent survey of 315 education institutions in five countries identified the effective use of information technology as a source of competitive advantage in marketing international education. Information technology in its various forms is well placed to assist education institutions to become more competitive within international markets. The Internet and Technologically Mediated Learning offer a means of promoting, administering and delivering education services to international markets. Within the Asia-Pacific region the emerging economies are likely to make increasing use of information technology, making it feasible for universities and colleges to develop new marketing and teaching strategies. The use of information technology to deliver education services overseas may become necessary due to both the demands of the market and pressure from other suppliers who are willing to embrace the new technology. The potential of the Internet is examined and it is suggested that higher education institutions will need to invest in the new technology or be uncompetitive within global markets.